Review on Seawater Greenhouse: Achievements and Future Development - Bait-Suwailam, Tahani K.; Al-Ismaili, Abdulrahim M. (Recent Patents on Engineering, 2019)
Background: Seawater greenhouse (SWGH) is a technology established to overcome issues related to open field cultivation in arid areas like high temperatures and freshwater shortage. So far, five pilot Seawater greenhouses were built around the world; in Spain, United Arab Emirates, Oman, Australia and Somaliland. All the patents related to the Seawater greenhouse components and designs mentioned were reviewed. Methods: The Seawater greenhouse adopts the humidification-dehumidification (HDH) concept where evaporated moisture from saline water source is condensed to produce freshwater within the greenhouse body. Many advancements have been made throughout the past 25 years to optimize the Seawater greenhouse by means of structural improvement, heat distribution, condenser design and material, source of feed water and the evaporator via both trial-and-error and simulation approaches. The latter included numerical, mathematical, analytical and artificial neural network simulations. Various condenser designs were adopted in order to increase freshwater production to meet the irrigation demand of the seawater greenhouse. Results and Conclusion: To make the Seawater greenhouse self-sufficient in terms of energy production, the use of renewable energies and nonconventional sources was also investigated like the use of geothermal, solar and wind energy to produce electricity for the greenhouse operation and for other requirements as well. The use of reverse osmosis along with reverse electro dialysis to produce freshwater and electricity in the seawater greenhouse, was also one of the ideas suggested to improve and solve the associated constraints. Direct contact dehumidification is another development suggested to improve the condensation rate. This new approach seems to be very promising as it involves low capital, operation and maintenance costs, high freshwater production, and fouling- and corrosion-free.
Keywords: Seawater greenhouse